Renin-angiotensin blocker use is associated with improved cardiovascular mortality in Indian patients with mild-moderate chronic kidney disease—findings from the ICKD study - Prasad, Narayan; Yadav, Ashok Kumar; Kundu, Monica; Jaryal, Ajay; Sircar, Dipankar; Modi, Gopesh; Sahay, Manisha; Gopalakrishnan, Natarajan; Vikrant, Sanjay; Varughese, Santosh; Baid-Agrawal, Seema; Singh, Shivendra; et al. (Frontiers in Medicine, 2022)
Angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) are the antihypertensive drug class of choice in patients with chronic kidney disease (CKD). Head-to-head comparisons of the renal or nonrenal outcomes between ACEI/ARB users and nonusers have not been conducted in all population groups. We examined the renal and cardiovascular outcomes in users and nonusers enrolled in the Indian Chronic Kidney Disease (ICKD) Study. A total of 4056 patients with mild-moderate CKD were studied. Patients were categorized as ACEI/ARB users or nonusers. Major adverse kidney events [ESKD (end stage kidney disease), ≥50% decline in eGFR and kidney death], all-cause mortality, and cardiovascular mortality were analysed over a median follow-up period of 2.64 (1.40, 3.89) years between the two groups. Out of a total of 4056 patients, 3487 (87%) were hypertensive. The adjusted sub-hazard ratio (SHR) and 95 % CI for ACEI /ARB users was 0.85 (0.71, 1.02) for MAKE, 0.80 (0.64,0.99) for a 50% decline in eGFR, and 0.72 (0.58, 0.90) for ESKD. For cardiovascular mortality, ACEI/ARB users were at lower risk (SHR = 0.55, 95% CI: 0.34, 0.88). Diuretic users were at increased risk of all-cause mortality (HR = 1.95, 95% CI: 1.50, 2.53) and cardiovascular mortality (adjusted SHR = 1.73, 95% CI: 1.09, 2.73).There was non-significant association between the use of other antihypertensives and any of the end points. ACEI/ARB use is associated with slower rate of decline in eGFR in those with CKD stage 1-3. ACEI/ARB users had a significantly lower risk of renal outcomes, and cardiovascular mortality.